U UPAYA MENINGKATKAN KEAKTIFAN DAN SEMANGAT BELAJAR SISWA KELAS IV SEKOLAH DASAR MELALUI MODEL PROBLEM BASED LEARNING - cindy oktaviana (Jurnal Dharma PGSD, 2025)
This study aims to enhance the active engagement and learning enthusiasm of fourth-grade elementary school students through the implementation of the Problem-Based Learning (PBL) model. Low levels of student engagement and enthusiasm during the learning process constitute a problem that can hinder the achievement of learning objectives. This study employed Classroom Action Research (CAR) involving 25 fourth-grade elementary school students. Data were collected through observation, interviews, and documentation to assess changes in student engagement and enthusiasm following the implementation of the Problem-Based Learning model. The results indicate that the Problem-Based Learning model successfully increased students' active participation in learning. Students became more enthusiastic about learning activities, more active in discussions, more confident in expressing their opinions, and capable of collaborating to solve problems assigned by the teacher. Learning also became more meaningful as the material was linked to issues relevant to the students' daily lives. Thus, the Problem-Based Learning model serves as an effective solution for boosting the engagement and enthusiasm of elementary school students, making the learning process more active, creative, and meaningful. Keywords: PBL, Study, Elementay School